PERAN INTERPOL DALAM MEMBERANTAS SINDIKAT CYBERSEX DI FILIPINA 2012-2014 - Ramondito, Bagus Wahyu; Hanura, Marten; Windiani, Reni (Journal of International Relations, 2015)
Various cybersex actions undertaken by syndicate in Philippines areinternational crimes which have threatened international peace andsecurity. Cybersex, which is part of cybercrime, becomes severeproblem in Philippines because it has harmed many people in thestate and even in other countries. This condition raised the presidentof Philippines, Benigno Aquino III’s concern, thus enacted law tocriminalize cybersex in Cybercrime Prevention Act of 2012.Responding to the law, The Philippine National Police (PNP)applies various rules to combat the cybersex syndicate, incooperation with other national polices under INTERPOL. Thisundergraduate thesis aims to seek the role of INTERPOL towardsthe cybersex in Philippines. This is an analythical descriptiveresearch using liberalism and differential association theory toanalyze the data founded by employing literature study method. Theresult of this research shows that INTERPOL lead the operations tocombat cybersex syndicate in Philippines.